Status Gizi, Asupan Zat Gizi Makro Serta Serat, dan Aktivitas Fisik Dengan Kebugaran Anak Sekolah Dasar Kelas V Usia (10-12 Tahun) di SDN Talaga 2 Cikupa Tangerang - Alawiyah, Tuty; Sugeng, Wiyono; Kuswari, Mury (Lembaga Penerbitan Unversitas Esa Unggul, 2015)
AbstractBackground: physical fitness everyone relate with physical health. One of the problems faced by groups of school-age children is the low level of health and nutritional status. Nutritional problems that developed in the community is very closely related to the behavior and lifestyle in childhood and adolescence. Physical fitness is influenced by several things, including nutrient intake, physical activity and body composition. Body composition was influenced by the magnitude of the nutritional status of a person. Objective: To determine the relationship of nutritional status, as well as the macro-nutrient intake and fiber, physical activity on physical fitness the fifth grade of primary school children aged (10-12 years) in SDN Talaga 2 Cikupa Tangerang. Methods: Respondents in this study amounted to 50 people aged 10-12 years. Variables tested were age, gender, nutritional status, as well as the macro-nutrient intake and fiber, physical activity, and physical fitness. Data processing is performed by Pearson correlation test and independent t-test. Results: The results showed that the correlation test variables associated with the physical fitness are gender, energy intake, and fat intake (p<0,05). Other variables such as age, nutritional status, protein intake, KH intake, fiber intake, and physical activity was not associated with physical fitness levelsfifth grade elementary school children aged 10-12 years in SDN Talaga 2 Cikupa Tangerang (p>0,05). Conclusions: Variables related to fitness is sex, energy intake, and fat intake.Â Keywords: nutritional status, nutrient intake, physical activityÂ AbstrakLatar Belakang: Kebugaran jasmani seseorang berhubungan dengan kesehatannya. Salah satu masalah yang dihadapi kelompok anak usia sekolah adalah rendahnya tingkat kesehatan dan keadaan gizi. Masalah gizi yang berkembang di masyarakat sangat erat hubungannya dengan perilaku dan gaya hidup pada masa kanak-kanak dan remaja. Kebugaran jasmani dipengaruhi oleh beberapa hal, diantaranya asupan zat gizi, aktivitas fisik dan komposisi tubuh.Komposisi tubuh tersebut dipengaruhi oleh besarnya status gizi seseorang. Tujuan: Mengetahui hubungan status gizi, asupan zat gizi makro serta serat, dan aktivitas fisik dengan kebugaran anak sekolah dasar kelas V usia (10-12 tahun) di SDN Talaga 2 Cikupa Tangerang. Metode: Responden dalam penelitian ini berjumlah 50 orang berusia 10-12 tahun. Variabel yang diuji yaitu umur, jenis kelamin, status gizi, asupan zat gizi makro serta serat, aktivitas fisik, dan kebugaran. Pengolahan data yang dilakukan dengan uji korelasi pearson dan uji t-test independent. Hasil: Hasil penelitian uji korelasi menunjukkan bahwa variable yang berhubungan dengan tingkat kebugaran adalah jenis kelamin, asupan energi, dan asupan lemak (p<0,05). variabel lainnya seperti umur, status gizi, asupan protein, asupan KH, asupan serat, dan aktivitas fisik tidak berhubungan dengan tingkat kebugaran anak sekolah dasar kelas V usia 10-12 tahun di SDN Talaga 2 Cikupa Tangerang (p>0,05). Kesimpulan:Variabel yang berhubungan dengan kebugaran adalah jenis kelamin, asupan energi, dan asupan lemak.Kata Kunci : status gizi, asupan zat gizi, aktivitas fisik